Challenges and Way Forward in a Transitional Period of Banking: Conventional to the Digital Era of Bangladesh - Samia Tahsin; Md. Matiur Rahman (CenRaPS Journal of Social Sciences, 2022)
This article narrates the current challenges experienced by Bangladesh's banking structure while developing the new generation banking system. They discuss subtopics such as technological infrastructure, security solutions, financial literacy, policies and legal frameworks, and customer cues towards embracing and using technologies. The research model critically discusses the above challenges and their interdependencies with the help of current literature and real-life data. The above sections of this research offer a comprehensive framework to address this change. This paper identifies key policy recommendations to address these challenges, such as technology adoption, improving cyber security, raising financial literacy levels, modifying the existing legal frameworks progressively, and increasing customers’ acceptance of digital banking solutions. By adopting these proposals, Bangladesh can subdue the challenges of digital transformation in banking and attain the potentiality for financial enfranchisement and economic emergence.